Pelatihan Pertanian Organik pada Lahan Pekarangan dan Pengaplikasian Biopori sebagai Upaya Ketahanan Pangan di Desa Wonosari Kecamatan Gondangrejo Kabupaten Karanganyar - Khadafi, Muhammad Sadam; Kurniawan, Muhammad Rizqi; Yudhanta, Muhammad Yanuar; Abdulloh, Muharom Zuhri; Destiaputri, Nabila Maharani; Azalia, Nazhiro; Kirana, Nessa Putri; Furoidah, Nizmah; Saputro, Pratama Galih; Saputri, Rahma Amani; Widadie, Fanny (PPPM POLTESA, 2024)
Agriculture plays an important role in maintaining and improving food security. Population growth has consequences for increasing food needs. The problem of national food security is a problem that must be solved together. Solving this problem requires the active role of the community, especially farmer groups through optimization of home yard land. The issues in the community are related to the concept of utilizing yard land, namely the lack of information and preparation of planting media, manure, and utilization of waste and materials in the surrounding environment. Therefore, these problems need to be resolved through community service activities related to optimizing yard utilization and applying bio pores. The methods used in the activities are lectures, reflections, and direct practice. The results show that the typical level of member information before the meeting increased from 26.7% to 96.7% after the socialization of yard land utilization was conducted. In addition, farmers' knowledge regarding the use and application of biopores before the meeting also increased by 10% to 93.3% after the socialization was carried out. Based on the results of the activities that have been carried out, this community service activity can increase the knowledge and skills of farmer group members about the importance of utilizing yard land through the application of organic vegetable cultivation accompanied by the application of bio pores for the utilization of organic waste.